The Use of Social Media Platforms in Implementing Quality Improvement Initiatives for Quality Assurance of Paediatric Chest Radiographs in Radiological Departments of Varying Radiographer Expertise - Hlabangana, Linda Tebogo (University of the Witwatersrand, Johannesburg, 2024)
Introduction Chest radiographs are the most widely performed diagnostic imaging test in children. Good quality radiographs assist in making the correct diagnosis. In resource limited settings, such as in Africa, there are several limiting factors that affect the quality of the radiograph which go beyond the availability of equipment and human resources, including geopolitical and socioeconomic challenges. Novel innovations are required to overcome these challenges by leveraging off technology and the widespread distribution of smart phones. Aim The aim of the study was to evaluate the improvement in the quality of chest radiographs performed in children after initiating quality improvement interventions at three radiology departments. The interventions used the Internet, Facebook® and Twitter®) to remotely communicate with the radiographers. Methods A longitudinal, descriptive study was performed at three radiological centres in South Africa. They study had a retrospective phase (before intervention), and a prospective phase. Over a period of six months, communication on quality factors of chest radiographs and how to improve quality were sent out using Facebook and Twitter. Thereafter, radiographs were collected and the quality assessed. Results A total of 966 radiographs were included in the study. The most common errors overall were “scapula in the way” (38.7%), “rotation” (34.7%) and “poor collimation” (22.2%). The errors “parts cut off” (1.3%) and “wrong/no left/right marker” (1.7%) were the least common. Rahima Moosa Mother and Child Hospital demonstrated non-significant improvement in the quality of radiographs over the duration of the study. The other two centres demonstrated no significant or sustained improvement in the quality of chest radiographs performed. The research did not demonstrate a significant benefit from the intervention. There was vi low engagement with the social media platforms. A total of six radiographers followed the Twitter handle and the Facebook page had 37 friends/followers, eight of these were radiographers participating in the study. Conclusions Although social media have demonstrated impactful use in education and communication, the usage by radiographers in South Africa to improve the quality of chest radiographs is limited. . There was no significant benefit demonstrated from the use of Facebook and Twitter as educational and information tools. Further research using low-data consumption social media apps to create locally relevant and sustainable solutions for quality assurance and quality improvement in radiography are required.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Quality assurance; social media; Facebook; Twitter; SDG-3: Good health and well-being